Komposisi Motif dan Warna Ragam Hias Pucoek Oen Nilam pada Tudung Saji Khas Aceh Jaya - Barend Naftali Nur Keusuma; Haikal Zuhri; Risky Fitriani; Syarifa Iza Muizah; Lestari Damayanti; Fatiya Zamira; Ismawan Ismawan (Jurnal Riset Rumpun Seni, Desain dan Media, 2023)
This research is entitled “Composition of motifs and colors of Pucoek Oen Nilam decorative motifs on Aceh Jaya's traditional food covers”. The formulation of the problem in this research is How is the composition of motifs and colors of Pucoek Oen Nilam decorative motifs on Aceh Jaya's traditional food covers. The purpose of this research is to describe the composition of motifs and colors of Pucoek Oen Nilam decorative motifs on Aceh Jaya's traditional food covers. The subject of this research is Mak Leot Aisyah, as a food cover craftsman. The object of this research is the composition of Pucoek Oen Nilam decorative motifs on food covers in Aceh Jaya. Data were obtained using observation, interview, and documentation techniques. The analysis used was to reduce the data first, then present it in the form of a brief description and finally verify it. The results of the research show that in terms of form, this motif falls into the category of floristic or fegetal motifs, realized from imitation of plant parts, such as leaves, flowers, fruit, roots, or tendrils with a visual stylization process. The composition of the Pucoek Oen Nilam motif on the serving hood is highly structured with a repetitive rhythm pattern with an asymmetrical balance with a visual hierarchy structure where the top of the serving hood has a negative space with several Pucok Oen Nilam motifs arranged at wide intervals and the bottom is compacted with the Oen Nilam motif.